Analisis Variasi Spasial a- dan b-Value Sebagai Indikator Kegempaan di Wilayah Nusa Tenggara bagian Timur - Rahmadani, Putri Amindar; Risky Martin Antosia; Anas Fauzi Masykuri; Putu Pradnya Andika (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
Eastern Nusa Tenggara, encompassing Timor, Flores, Alor, and Kupang City, lies along the active collision zone between the Indo-Australian and Eurasian plates, making the region highly susceptible to earthquakes. This study analyzes the spatial variation of a-value and b-value based on the earthquake catalog from 1998–2023 using ZMAP v.6.0 software. The frequency–magnitude distribution (FMD) curve indicates an inverse relationship between earthquake frequency and magnitude. Spatially, relatively high b-values are observed in eastern Flores to Alor, indicating frequent seismic activity with low released energy, while the variation of a-value reflects the level of seismicity, ranging from 5.0–6.0, with b-values between 0.8–1.1. These findings provide valuable insights for disaster mitigation, infrastructure planning, and enhancing community preparedness in Eastern Nusa Tenggara, including Kupang City.